Modalitas Budaya Sebagai Potensi Cultural Heritage Tourism: Studi Reflective Observation Dusun Cipanjalu, Desa Palintang, Kecamatan Ciporeat, Kabupaten Bandung - Ramlan, Ramlan; Dewi, Agustina Kusuma (Jurnal Desain Indonesia., 2025)
This article discusses the role of cultural modalities in the development of cultural heritage tourism with a case study in Cipanjalu Hamlet, Palintang Village, Ciporeat District, Bandung Regency. The main aim of the research is to understand how local cultural modalities contribute to the management and promotion of cultural heritage tourism, as well as their impact on economic sustainability and preservation of local culture. With a scientific perspective on Visual Communication Design in the competency areas of Visual Culture and Cultural Heritage Conservation; This research is qualitative research with an observational-reflective approach referring to the Kolb Model. The research results show that cultural modalities such as traditions based on literature and culinary in Cipanjalu Hamlet are built between local community legends and traditional ways of life - have the potential to attract tourists and can support efforts to strengthen local cultural identity in the Era of Society 5.0. However, facing the challenges of the onslaught of information and open communication technology, it was also concluded that challenges such as sustainable management, cultural preservation and community participation remain the main focus. in promoting sustainable tourism and preserving valuable cultural heritage. Key words: cultural heritage, cultural modalities, cultural preservation